Ventilation of the Deep Ocean Carbon Reservoir During the Last Deglaciation: Results From the Southeast Pacific - Martinez Fontaine, Consuelo; De Pol Holz, Ricardo Hernán; Michel, Elisabeth; Siani, Giuseppe; Reyes-Macaya, Dharma; Martinez-Mendez, Gema; DeVries, Tim; Stott, Lowell; Southon, John; Mohtadi, Mahyar; Hebbeln, Dierk (My University, 2019)
Coeval changes in atmospheric CO2 and C-14 contents during the last deglaciation are often attributed to ocean circulation changes that released carbon stored in the deep ocean during the Last Glacial Maximum (LGM). Work is being done to generate records that allow for the identification of the exact mechanisms leading to the accumulation and release of carbon from the oceanic reservoir, but these mechanisms are still the subject of debate. Here we present foraminifera C-14 data from five cores in a transect across the Chilean continental margin between similar to 540 and similar to 3,100 m depth spanning the last 20,000 years. Our data reveal that during the LGM, waters at similar to 2,000 m were 50% to 80% more depleted in Delta C-14 than waters at similar to 1,500 m when compared to modern values, consistent with the hypothesis of a glacial deep ocean carbon reservoir that was isolated from the atmosphere. During the deglaciation, our intermediate water records reveal homogenization in the Delta C-14 values between similar to 800 and similar to 1,500 m from similar to 16.5-14.5 ka cal BP to similar to 14-12 ka cal BP, which we interpret as deeper penetration of Antarctic Intermediate Water. While many questions still remain, this process could aid the ventilation of the deep ocean at the beginning of the deglaciation, contributing to the observed similar to 40 ppm rise in atmospheric pCO(2).
Keywords: Deglaciation; Last Glacial Maximum